Guillain-Barre Syndrome Associated with Disseminated Tuberculosis: A Case Report - Elsa Primadona Sulfana Putri; Idzni Mardhiyah; Sri Wahyu Evianti (Magna Neurologica, 2025)
Background: Guillain-Barre syndrome (GBS) is a life-threatening, acute, immune-mediated polyneuropathy associated with preceding infections. Tuberculosis (TB), although it has a high incidence rate, is rarely reported to be associated with GBS. Case: We report the case of a 20-year-old female admitted to our hospital with a progressive symmetrical paraparesis, which further developed to paraplegia, along with a month-long history of constitutional symptoms. After investigation, the patient was diagnosed with an acute motor and sensory axonal neuropathy (AMSAN) variant of GBS and disseminated TB. The patient was treated with plasmapheresis, and first-line anti-tuberculosis therapy was initiated. The patient demonstrated significant improvement in muscle strength in response to the treatment. The pathogenesis of GBS in TB is believed to be due to molecular mimicry, leading to nerve damage or direct invasion of the nerve root by tubercular bacilli. Discussion: Guillain-Barre syndrome could be induced by tuberculosis, and treatment for both could improve the outcome. Thus, early diagnosis is critical. Further investigations must be conducted to understand the association of GBS and TB. Conclusion: Guillain-Barre syndrome could be induced by tuberculosis, and treatment for both could improve the outcome. Thus, early diagnosis is critical. Further investigations must be conducted to understand the association of GBS and TB.